Le Dictionnaire caraïbe-français du dominicain Raymond Breton : témoignage de tensions interculturelles - Marie-Christine Pioffet (Journal de la Société des Américanistes)
Raymond Breton’s Dictionnaire caraïbe-français, first published in 1665, includes a montage of sentences and conversations held by the Dominican and the islanders of Guadeloupe. More than a linguistic tool, this work constitutes a first-rate testimony to the morals and customs of the country’s natives. Despite the efforts of rapprochement made by the missionary, the present investigation shows that the extracts in local language and the anecdotes reported reflect intercultural tensions and resistance of the natives in the face of the Dominican’s evangelization enterprise. The Caribbean statements recorded, evidently captured on the spot, clearly reveal the cultural gap that separates the visitor from his hosts, who are hostile to his teaching. For today’s researchers, the Dictionary therefore appears not only as a complement to Father Breton’s missionary relationships, but also as an essential source for reconstructing this episode in the history of Guadeloupe and the often conflicting relationships between the missionary and the Caribbeans.